Religiosity, Attitudes, and Financial Literacy as Predictors of Saving Behavior: The Mediating Role of Saving Intention among Muslim Young Generation - Siti Kholifah; Maulida Nurul Innayah; Naelati Tubastuvi; Nawalin Nazah (Jurnal Ekonomi Pembangunan, 2025)
This study aims to examine the influence of religiosity, attitude towards saving, and financial literacy on saving behaviour, with saving intention as a mediating variable among Muslim Generation Z in Banyumas Regency. Using a quantitative approach with purposive sampling, data were collected from 139 respondents and analysed using SEM-PLS in SmartPLS 4.0. The results show that attitude towards saving has a significant positive effect, both directly and indirectly through saving intention, on saving behaviour, while religiosity and financial literacy do not demonstrate significant effects. These findings suggest that psychological factors, specifically attitudes and intentions, play a more substantial role in shaping saving behaviour than religious values or financial knowledge. The study concludes that strengthening positive attitudes toward saving is essential for improving financial behaviour among young Muslims. However, the generalizability of the results remains limited due to the narrow geographical scope of the sample.